Pengaruh Lokasi, Jarak Central Business District, dan Aksesibilitas terhadap Nilai Wajar Sewa Penempatan Mesin ATM di Kota Manado, Indonesia - Partoho, Goklas Tunggul; Nadir, Rasyidah; Gaffar, Ismail (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2024)
AbstractState property (BMN) that have not been optimized for use can be utilized by others, one of which is banking companies as an effort to improve services through investment in the placement of ATM machines in certain locations according to corporate needs plans without reducing the Standard of Goods and Standard Needs (SBSK), and the quality of service based on the main duties and functions of each ministry/institution.  The determination of the amount of rent for the utilization of BMN as a contribution to Non-Tax State Revenue (PNBP) is based on the fair value of rent determined by the Government Assessor.  This study aims to examine the effect of location, CBD distance, and accessibility on the fair value of ATM machine placement rent based on a quantitative approach with data collection methods through field survey techniques on 45 ATM rental data in Manado City.  Meanwhile, the analysis technique used is Multiple Regression Analysis with data processing through the Eviews 10 (Econometric Views) program.  The results showed that the test value of the R Square Coefficient of Determination was equal to 0.5581 or 55.81% of the independent variable in this study was able to explain the dependent variable, while the remaining 44.19% was explained by other variables that were not included in this study and the error value.  It was concluded that simultaneously location, CBD distance, and accessibility positively affect the fair value of ATM machine placement rent. Keywords: Location; CBD distance; Accessibility; Fair Value of Rent; ATM  @font-face {font-family:Cardo; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:none; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; color:black; mso-font-kerning:14.0pt; mso-fareast-language:IN;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-fareast-language:IN;}.MsoPapDefault {mso-style-type:export-only; mso-pagination:none;}div.WordSection1 {page:WordSection1;}div.WordSection2 {page:WordSection2;}div.WordSection3 {page:WordSection3;}